2024
DOI: 10.1186/s12967-024-05044-7
|View full text |Cite
|
Sign up to set email alerts
|

Impaired balance between neutrophil extracellular trap formation and degradation by DNases in COVID-19 disease

Geoffrey Garcia,
Sylvie Labrouche-Colomer,
Alexandre Duvignaud
et al.

Abstract: Background Thrombo-inflammation and neutrophil extracellular traps (NETs) are exacerbated in severe cases of COVID-19, potentially contributing to disease exacerbation. However, the mechanisms underpinning this dysregulation remain elusive. We hypothesised that lower DNase activity may be associated with higher NETosis and clinical worsening in patients with COVID-19. Methods Biological samples were obtained from hospitalized patients (15 severe, 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…While de Diego and colleagues reported that only cell‐free DNA in the plasma but not other NET markers correlated with disease severity, 12 other studies have shown the association of multiple markers of NET with severe COVID‐19. 4 , 13 , 14 Our recent study also indicates that mature neutrophils with heightened activation phenotype remained in circulation for up to 6 months in PASC patients with persistent pulmonary sequelae. 15 Therefore, it is essential to identify clinically relevant NET markers that are highly associated with post‐COVID pulmonary fibrosis and test them as therapeutic targets.…”
Section: Figurementioning
confidence: 74%
“…While de Diego and colleagues reported that only cell‐free DNA in the plasma but not other NET markers correlated with disease severity, 12 other studies have shown the association of multiple markers of NET with severe COVID‐19. 4 , 13 , 14 Our recent study also indicates that mature neutrophils with heightened activation phenotype remained in circulation for up to 6 months in PASC patients with persistent pulmonary sequelae. 15 Therefore, it is essential to identify clinically relevant NET markers that are highly associated with post‐COVID pulmonary fibrosis and test them as therapeutic targets.…”
Section: Figurementioning
confidence: 74%